Analisis Komparasi Kemampuan Membaca Al-Qur’an Siswa Kelas XI dengan Metode Iqro’ dan Metode Baghdadi di SMA Negeri 2 Batang Anai - Refki Romadani; Sulaiman, Sulaiman (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This research is motivated by students who are still not fluent in reading the Qur'an, hence the importance of using learning methods to improve students' ability to read the Qur'an at SMA Negeri 2 Batang Anai. The objective of this research is to determine the comparison between the Iqro’ method and the Baghdadi method in improving students' abilities in reading the Qur'an. The method used is quantitative research with a pre-test, post-test, non-equivalent multiple group design, involving two experimental classes to see the effect of variable X on variable Y selected through purposive sampling technique. Data were collected through tests, observation, and documentation, then analyzed statistically through data collection, descriptive tests, classical assumption tests, hypothesis tests, and n-gain score tests, and conclusions were drawn. The research results show that both methods provide a statistically significant improvement in the ability to read the Qur'an. However, the Iqro' method shows a higher improvement compared to the Baghdadi method, with an average N-Gain Score of 23.43%, while the Baghdadi method is at 20.38%. Nevertheless, based on the effectiveness classification, both methods are still in the low category. Thus, it can be concluded that the Iqro' method is more effective than the Baghdadi method in enhancing students' Qur'an reading skills, although the improvement has not yet reached a high category. This finding is expected to provide input in choosing more appropriate and measurable Qur'an learning methods in high school environments.